LITERASI KEUANGAN, RELIGIUSITAS DAN PENGARUHNYA TERHADAP PENGELOLAAN KEUANGAN MAHASISWA - Hesty Utami, Ratih; Arsika Ndriana, Rescy; Indriasari, Ika (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This study aims to analyze the effect of financial knowledge, religiusity, financial attitudes, an financial literacy on student financial management. Respondent in this study were management students of the University PGRI Semarang with a total of 254 respondents. Data gathering process is conducted with a way of data retrieval online through the deployment of questioning. This study uses quantitative methods with data collection techniques through questionnaires. The method used in this study is multiple linear regression analysis. The result of this study indicate that there is a positive and significant influence between financial knowledge on financial management, there is a positive and significant influence between religiosity on financial management, there is a positive and significant influence between financial attitudes on financial management, and there is a positive and significant influence between financial literacy on financial management. Financial knowledge, religiosity, financial literacy effect on financial management simultaneously. Based on the result of the research that has been done, the R Square value is 0.696 or 69.6%. While the remaining 0.306 or 30.6% is influenced by other variables not examined in this study.